ANALISIS KETERAMPILAN PROSES SAINS TERINTEGRASI DALAM PEMBELAJARAN FISIKA PADA SISWA SMK NEGERI 5 JEMBER KELAS X MATERI SUHU DAN KALOR - Uzlifatul Jannah; Sri Handono B,P; Subiki Subiki (JURNAL PEMBELAJARAN FISIKA, 2018)
Science process skills are important for student as preparation and practice in facing the reality of life in society, students are trained to think logically in solving a problem. The purpose of this study was to analyze integrated science process skills in students of SMK Negeri 5 Jember class X material temperature and heat. The type of research used is descriptive research with a sample of 130 students in class X APH 1, X APH 2, X APL 2, and X TKJ 1 in SMK Negeri 5 Jember. Result of research indicate that integrated process skill at class X APH 1 included in category less with percentage average 59,13%, class X APH 2 included in category enough with presentation average 73,53%, class X APL 2 included in category enough with an average percentage of 67.53%, and class X TKJ 1 included in the category enough with an average percentage of 68.08%. the overall average is 68.08% included in the category enough. It can be generally known that the skill of the integrated science process of students of SMK Negeri 5 jember class X temperature and heat materials are included on sufficient criteria.Keywords: integrated science process skills, temperature, heat